2017
DOI: 10.3389/fimmu.2017.00601
|View full text |Cite
|
Sign up to set email alerts
|

TNF Lectin-Like Domain Restores Epithelial Sodium Channel Function in Frameshift Mutants Associated with Pseudohypoaldosteronism Type 1B

Abstract: Previous in vitro studies have indicated that tumor necrosis factor (TNF) activates amiloride-sensitive epithelial sodium channel (ENaC) current through its lectin-like (TIP) domain, since cyclic peptides mimicking the TIP domain (e.g., solnatide), showed ENaC-activating properties. In the current study, the effects of TNF and solnatide on individual ENaC subunits or ENaC carrying mutated glycosylation sites in the α-ENaC subunit were compared, revealing a similar mode of action for TNF and solnatide and corro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Progesterone has been shown in some studies to decrease recurrent miscarriage by balancing the Th1/Th2 cytokines [ 24 ]. Several studies have shown that residues Cys101-Glu116 play an essential role at the binding site of TNF-α [ 25 ]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone has been shown in some studies to decrease recurrent miscarriage by balancing the Th1/Th2 cytokines [ 24 ]. Several studies have shown that residues Cys101-Glu116 play an essential role at the binding site of TNF-α [ 25 ]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have also shown that in A549 cells TNF can positively increase single channel kinetics without affecting conductivity of the channel and this increase was completely abolished in PNGase F pretreated cells [ 13 ]. Glycosylation sites on the ENaC subunits are necessary for TNF-induced activation of ENaC current and membrane insertion [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solnatide mainly activates the pulmonary epithelial sodium channel and restores the injured endothelial-epithelial barrier of pulmonary alveoli. 23,24 In 2013, APEPTICO fruitfully concluded phase 1 clinical study in healthy subjects, verifying the safety of solnatide. Additionally, APEPTICO also effectively finished a randomized, doubleblinded placebo-controlled phase 2 clinical trial in mechanically ventilated ARDS patients with lung oedema, proving the purpose of inhaled solnatide.…”
Section: Inhaled Solnatidementioning
confidence: 96%